2020
DOI: 10.1039/d0dt03669b
|View full text |Cite
|
Sign up to set email alerts
|

A pentazolate-based bowl-shaped molecular container

Abstract: Molecular containers, which are capable of capturing or encapsulating guests, have attracted significant attention, and as a superior nitrogen-donor bridging ligand, the isolated cyclo-N5- anion shows its enormous potential for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Different attempts have been conducted to explore characteristic N 5 – -derived frameworks. In our continuous efforts, we detected that the slight alterations of external conditions might induce various pentazolate assemblies with varying topologies . The introduction of appropriate solvents or additives could observably regulate the crystallization behaviors of NaN 5 salts and thus influence the crystal structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different attempts have been conducted to explore characteristic N 5 – -derived frameworks. In our continuous efforts, we detected that the slight alterations of external conditions might induce various pentazolate assemblies with varying topologies . The introduction of appropriate solvents or additives could observably regulate the crystallization behaviors of NaN 5 salts and thus influence the crystal structures.…”
mentioning
confidence: 99%
“…The pentazolium salts of the same composition may form a variety conditions might induce various pentazolate assemblies with varying topologies. 28 The introduction of appropriate solvents or additives could observably regulate the crystallization behaviors of NaN 5 salts and thus influence the crystal structures. Herein, we have presented two new sodiumpentazolate frameworks, namely, MPF-3 and MPF-4 (Figure 1c,d), which are obtained by adjusting the exterior conditions.…”
mentioning
confidence: 99%
“…Our group reported a series of metal-N 5 − hydrates, including [Na(H 2 O)(N 5 )]·2H 2 O, [M(H 2 O) 4 (N 5 ) 2 ]·4H 2 O (M = Mn, Fe, Co, and Zn) and [Mg(H 2 O) 6 (N 5 ) 2 ]·4H 2 O, which confirmed that cyclo -N 5 − can be coordinated and stabilized by metal cations and opened up a promising path for fascinating pentazole chemistry. 16 Gradually, many metal-N 5 − coordination polymers (CPs) have been reported, including [Na 8 (N 5 ) 8 (H 2 O) 3 ] n , 17 MPF-1, 18 [Ba(N 5 )(NO 3 )(H 2 O) 3 ] n , 19 [NaBa 3 (N 5 ) 6 (NO 3 )(H 2 O) 3 ] n , 19 [Cu(N 5 )(N 3 )] n , 19 [Ag(N 5 )] n , 19 [Ag(NH 3 ) 2 ] + [Ag 3 (N 5 ) 4 ] − , 20 [LiNa(N 5 ) 2 (H 2 O) 4 ]·H 2 O, 21 KN 5 , 22 Na 5 (N 5 ) 5 (H 2 O) 2 (MSN)·DMSO (MPF-2), 23 MPF-3, 24 and Na 3 (N 5 ) 3 [SO 2 (CH 3 ) 2 ] (MPF-4). 24…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Until 2017, 15,16 breakthrough progress was made in the bulk synthesis and isolation of cyclo- and opened up a promising path for fascinating pentazole chemistry. 16 Gradually, many metal-N 5 − coordination polymers (CPs) have been reported, including [Na 8 (N 5 ) 8 (H 2 O) 3 ] n , 17 MPF-1, 18 [Ba(N 5 )(NO 3 )(H 2 O) 3 ] n , 19 [NaBa 3 (N 5 ) 6 (NO 3 )(H 2 O) 3 ] n , 19 [Cu(N 5 )(N 3 )] n , 19 [Ag(N 5 )] n , 19 [Ag(NH 3 ) 2 ] + [Ag 3 (N 5 ) 4 ] − , 20 [LiNa (N 5 ) 2 (H 2 O) 4 ]•H 2 O, 21 KN 5 , 22 Na 5 (N 5 ) 5 (H 2 O) 2 (MSN)•DMSO (MPF-2), 23 MPF-3, 24 and Na 3 (N 5 ) 3 [SO 2 (CH 3 ) 2 ] (MPF-4). 24 Cyclo-N 5 − complexes have also been characterized in high pressure chemistry from the coupling of N 2 and metal azides (MN 3 ) or N 2 and metals.…”
mentioning
confidence: 99%
“…1). 12,13 As such, based on the coordination of cyclo-N 5 − with Na + , the introduction of auxiliary ligands will bring about the formation of NaN 5 frameworks with diverse topologies.…”
mentioning
confidence: 99%